The Demands of Professionalism: Discussing English Teacher Personality And The Impact on Character Building of Elementary School Students: English - chaniago, Anisah firly; Jihan Aldie Fathani; Nur Aini Agustina; Sally Dyah Kesuma Dewi (Yayasan Insan Cipta Medan, 2024)
This article discusses the key role of professionalism in shaping student character in elementary schools. The focus is on the aspect of teacher personality and its impact in shaping students' character. Teachers not only deliver subject matter, but also play a role as role models in children's character development. The requirements of professionalism, especially regarding teacher personality, affect teacher-student interactions and the learning context in the classroom. In the face of these challenges, this article explores the role of teachers as role models, the impact of teacher behavior on students' mindsets, and professional strategies to build positive character. The linkages between the requirements of professionalism, teacher personality and student character building are investigated to formulate concrete steps to improve the quality of education at the elementary level. Through a literature study, this research found that teacher professionalism significantly influences the quality of education, including students' character building and cognitive abilities. Continuous professional development for teachers is needed to improve students' overall educational experience. The research also highlights the level of student heterogeneity and the need for teachers to understand and identify students' individual characteristics to design effective learning programs.